2021
DOI: 10.1002/pbc.29425
|View full text |Cite
|
Sign up to set email alerts
|

Waitlist mortality and post‐liver transplant outcomes of pediatric patients with hepatocellular carcinoma and hepatoblastoma in the United States

Abstract: Background: Liver transplantation (LT) is offered in cases of advanced disease for both pediatric patients with hepatoblastoma (HBL) and those with hepatocellular carcinoma (HCC). Current United States organ allocation priorities differ between the two groups. Methods:We retrospectively examined the waitlist and posttransplant outcomes of pediatric LT candidates with HBL and HCC using the United Network for Organ Sharing registry (February 2002 to September 2020). Results: Six hundred sixty-eight children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Despite multiple comorbidities, post-liver transplant survival for patients with AGS is similar to that with biliary atresia 19. While the waitlist for paediatric liver transplant candidates with HCC is higher as compared with HB, post-transplant survival is the same 20. Although a review by Schindler et al suggested the need for surveillance for hepatocellular carcinoma in adult patients with AGS, there are no such recommendations for children 21.…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple comorbidities, post-liver transplant survival for patients with AGS is similar to that with biliary atresia 19. While the waitlist for paediatric liver transplant candidates with HCC is higher as compared with HB, post-transplant survival is the same 20. Although a review by Schindler et al suggested the need for surveillance for hepatocellular carcinoma in adult patients with AGS, there are no such recommendations for children 21.…”
Section: Discussionmentioning
confidence: 99%
“…Pertaining to organ availability, Wu et al reported an average waiting time of approximately 29 days on the transplant list for hepatoblastoma patients in the United States ( 11 ); nevertheless, there is decreased availability in developing countries. An analysis of Colombian data spanning from 2009 to 2017 indicated an all-age mean duration on the liver transplant waiting list of 4.6 months, extending up to a maximum of 8 months ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A recent analysis of HBL LT outcomes showed that the waitlist mortality for HBL is below 5%. 31 Nevertheless, management of these patients the waiting list can be challenging due to the unpredictable nature of deceased donor graft availability and the importance of optimizing receipt of effective chemotherapy in the neoadjuvant and adjuvant setting, hence emphasizing the need to evaluate the impact of donor graft type on post-transplant survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, as soon as the diagnosis of unresectable HBL is made, experts suggest that patients are initiated on neoadjuvant chemotherapy and referred for early LT evaluation if tumors remain unresectable, 27,28 provided that disease is limited to the liver or in the case of pulmonary metastases which resolve with resection and/or chemotherapy 29,30 . A recent analysis of HBL LT waitlist outcomes showed that the waitlist mortality for HBL is below 5% 31 . Nevertheless, management of these patients on the waiting list can be challenging due to the unpredictable nature of deceased donor graft availability and the importance of optimizing receipt of effective chemotherapy in the neoadjuvant and adjuvant setting, hence emphasizing the need to evaluate the impact of donor graft type on post‐transplant survival.…”
Section: Discussionmentioning
confidence: 99%